Biologic Activity of a Dinuclear Pd(II)-Spermine Complex Toward Human Breast Cancer - Fiuza, Sónia M. (2011)
A dinuclear palladium-based complex (Pd(2) -Spm) was synthesized and compared with cisplatin (cDDP) on two different human breast cancer cell lines (MCF-7 and MDA-MB-231) as well as toward an untransformed cell line (BJ fibroblasts). The results obtained show that Pd(2) -Spm is more effective against the estrogen receptors [ER(-)] cell line MDA-MB-231, while cDDP displayed better results for the ER(+) MCF-7 cell line. It was shown that, like cDDP, Pd(2) -Spm triggers phosphorylation of H2AX, indicating that this compound damages DNA. Apart from DNA, Pd(2) -Spm also targets the cytoskeleton having a greater impact on cell morphology than cDDP. Pd(2) -Spm and cDDP have opposite antiproliferative activities in the presence of the PI3K inhibitor wortmannin. Furthermore, Pd(2) -Spm at an optimized concentration displays a rapid antiproliferative effect as opposed to cDDP, which seems to have a slower kinetics. The results point to a distinct mechanism of action for each of these complexes, which may explain their synergistic action when coadministrated.